2011
DOI: 10.1093/eurheartj/ehr004
|View full text |Cite
|
Sign up to set email alerts
|

Influenza vaccination reduces cardiovascular events in patients with acute coronary syndrome

Abstract: The influenza vaccine reduced major cardiovascular events in patients with ACS. Therefore, it should be encouraged as a secondary prevention in this group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
139
1
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(157 citation statements)
references
References 25 publications
7
139
1
10
Order By: Relevance
“…[258] A recent study with similar methods among patients with acute coronary syndrome looked at a broader outcome of combined major cardiovascular events and found a significant hazards ratio of 0.70, but found no significant difference in cardiovascular deaths between the vaccine and control groups. [259] A 2008 Cochrane review of vaccine effects on patients with coronary heart disease included 2 trials and concluded that the small numbers of outcomes of interest, such as cardiovascular death and myocardial infarction, resulted in imprecise estimates and insufficient data to evaluate this association. [10] Compared to healthy populations, vaccine performance may be decreased in populations with underlying respiratory and/or cardiovascular diseases, and meta-analyses indicate that there is insufficient evidence to conclude that vaccines are adequately effective in these groups.…”
Section: Disease Burdenmentioning
confidence: 99%
“…[258] A recent study with similar methods among patients with acute coronary syndrome looked at a broader outcome of combined major cardiovascular events and found a significant hazards ratio of 0.70, but found no significant difference in cardiovascular deaths between the vaccine and control groups. [259] A 2008 Cochrane review of vaccine effects on patients with coronary heart disease included 2 trials and concluded that the small numbers of outcomes of interest, such as cardiovascular death and myocardial infarction, resulted in imprecise estimates and insufficient data to evaluate this association. [10] Compared to healthy populations, vaccine performance may be decreased in populations with underlying respiratory and/or cardiovascular diseases, and meta-analyses indicate that there is insufficient evidence to conclude that vaccines are adequately effective in these groups.…”
Section: Disease Burdenmentioning
confidence: 99%
“…Moreover, in mice, influenza propagates the inflammatory response, the progression and thrombosis of atherosclerotic plaques (Naghavi et al 2003). Influenza vaccination has been shown to be beneficial in reducing major cardiovascular events amongst acute coronary syndrome patients (Phrommintikul et al 2011). Furthermore, many other disparate acute and chronic pathogens, such as Clostridium pneumoniae (Vainas et al 2009), HIV (Ho and Hsue 2009), CMV (Simanek et al 2011) and gum disease-causing bacteria (Kebschull et al 2010), carry an elevated risk of CVD, suggesting that, rather than the nature of the infectious agent, it is the ensuing host-derived inflammatory response that drives this increased CVD risk.…”
Section: Seasonal Influenzamentioning
confidence: 99%
“…31,32 However, both of these RCTs enrolled a small number of patients, and thus may not have been sufficiently powered to detect a difference. Furthermore, small sample sizes may introduce confounding and bias, which may have resulted in overestimation of the true benefit for the RCTs with positive results.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31][32][33][34] Two of the RCTs were assessed to be of moderate quality and one was of low quality according to the GRADE criteria; quality assessment could not be performed for the remaining 2 RCTs, which have not been formally published in full-text.…”
Section: Randomized Controlled Trialsmentioning
confidence: 99%